Netnography Analysis of Halal Food Finder Applications - Alam, Azhar; Azhari, Fetri Dwifa; Fathma, Azizah; Nordin, Nadhirah (International Journal of Basic and Applied Sciences, 2025)
This study analyzes users' experiences and perceptions of halal food search applications using netnography on the Google Play Store. Six ‎applications with a minimum rating of 3.5 were selected. User reviews were collected by June 18, 2025, and included 179 reviews from six ‎different applications of Halal Food Finder. These reviews were then filtered into 163 reviews, comprising 134 positive reviews and 29 negative reviews. These were further analyzed. The results show that positive reviews are primarily driven by appreciation for informative ‎features, halal restaurant location indicators, support for Muslim travellers, and ease of use. On the other hand, negative reviews highlight ‎obstacles such as inaccurate data, feature updates needed, scan failures, local language limitations, and technical issues with the application. ‎The findings indicate that while feature innovations strengthen user trust, data accuracy and update sustainability are still challenges. Development recommendations include proposing partnerships with global halal certification bodies for periodic updates of verified halal certification data, improving technical stability, implementing database management, using artificial intelligence (AI) and blockchain for information ‎validation, and refining the interface to make the system more intuitive and user-friendly. The implementation of this step is expected to ‎strengthen the halal digital ecosystem by providing reliable, accurate, and responsive services to user needs.
Keywords: Digital Halal Ecosystem; Google Play Store; Halal Food Application; User Experience